PENGEMBANGAN MEDIA PEMBELAJARAN KATAR (KARTU PINTAR) PADA MATERI TEMBANG MACAPAT UNTUK SISWA KELAS V SD - Kristina Maisaroh; Nikmah Fitria Surya; Mutma’innah Nurizzah (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Katar (Smart Card) research is a learning medium for fifth-grade students at SDN Panglungan 1 which has been validated and then tested. Katar (Smart Card) is a media or visual aid in the form of a card made with an attractive appearance. The purpose of this research is to develop Katar (Smart Card) development media. This type of research is research and development. Researchers use this type of research, namely qualitative data. The development model used in this research is Addie's development model. The stages used are 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Data collection techniques used are questionnaires and questionnaires. The subjects of the study were fifth-grade students at SDN Panglungan 1. The results obtained were that the rotary wheel learning media obtained a validity percentage of 86% from material experts, 86% from media experts, and 85% practicality test from learning experts. Based on the product effectiveness test conducted, it was found that there was an increase above the KKM, namely 13 students out of 18 students scored above the KKM 86.65. So, it can be concluded that Katar media (Smart Cards) is feasible and effective to use.